Discontinuous Budget Constraints and Estimation: The Demand for Housing - Hausman, Jerry A.; Wise, David A. (Review of Economic Studies, 1980)
Jerry A. Hausman, David A. Wise; Discontinuous Budget Constraints and Estimation: The Demand for Housing, The Review of Economic Studies, Volume 47, Issue 1, 1